Nekdanja odlagališča odpadkov v vrtačah in gramoznicah - Breg Valjavec, Mateja (Geografija Slovenije, 2013)
This volume ('Former waste disposal sites in dolines and gravel pits') presents former waste disposal sites in depressions (dolines and gravel pits) using relief analysis of the former and current landscape and based on comparing them with one another. A comprehensive methodological approach has been created called the three-dimensional (3D) model, which is used to detect and record unknown, hidden former waste disposal sites in depressions above sensitive aquifers. The research deals with the problem of former waste disposal sites from the viewpoint of discovering them, creating a registry, and studying noticeable surface effects on the landscape (relief, soil, and vegetation).